Combination treatment with telitacicept, cyclophosphamide and glucocorticoids for severe Granulomatous polyangiitis: a case report and literature review - Huang, Liqi; Lin, Wenjian; Liu, Yu; Zhu, Junfeng; Li, Yun; Zheng, Zhihua; Tang, Chun (Frontiers in Immunology, 2023)
Granulomatous polyangiitis (GPA) is a rare autoimmune disease that can involve multiple systems throughout the body, including the ear, nose, upper and lower respiratory tracts. It is classified as an antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis. Telitacicept is a novel recombinant fusion protein targeting B-lymphocyte stimulator (BLyS). Telitacicept can inhibit the development and maturation of abnormal B cells by blocking BLyS, and inhibit the production of antibodies by abnormal plasma cells by blocking APRIL (A proliferation-inducing ligand), which is expected to become a new drug for the treatment of GPA. We report a 64-year-old man diagnosed at our hospital with GPA involving multiple systems including kidneys, lungs, nose and ears. Renal involvement was severe, with a clinical characteristic of rapidly progressive glomerulonephritis and a pathologic manifestation of crescentic nephritis with plasma cell infiltration. The patient was treated with hormones, immunoglobulins and cyclophosphamide (CYC) with the addition of telitacicept and a rapid reduction in hormone dosage. The patient's renal function improved significantly within a short period of time, and his hearing and lung lesions improved significantly. At the same time, he This is a provisional file, not the final typeset article did not develop serious infections and other related complications. Our report suggests that shortterm control of the patient's conditions is necessary in GPA patients with organ-threatening disease. Telitacicept combined with CYC and glucocorticoids may be an induction therapy with safety and feasibility. However, more clinical trials are needed to validate the efficacy and safety of the therapeutic regimen.